Microwave-hydrothermal synthesis of single-crystalline Co3O 4 spinel nanocubes - Mulinari, Tatiana A. [UNESP]; La Porta, Felipe A. [UNESP]; Andrés, Juan; Cilense, Mário [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Royal Society of Chemistry (RSC), 2013)
An efficient microwave-hydrothermal (MAH) method has been developed for the synthesis of highly crystalline Co3O4 spinel nanocubes via β-Co(OH)2 without any surfactant assistance. The structure and surface chemical composition along the growth process are studied. The effects as well as the merits of the MAH method on the processing and characteristics of obtained Co3O4 spinel nanocubes are highlighted. © 2013 The Royal Society of Chemistry.